2024
DOI: 10.1128/spectrum.03270-23
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and TMPRSS2 distribution in the respiratory tract of different animal species and its correlation with SARS-CoV-2 tissue tropism

Mariano Carossino,
Sudeh Izadmehr,
Jessie D. Trujillo
et al.

Abstract: A wide range of animal species show variable susceptibility to SARS-CoV-2; however, host factors associated with varied susceptibility remain to be defined. Here, we examined whether susceptibility to SARS-CoV-2 and virus tropism in different animal species are dependent on the expression and distribution of the virus receptor angiotensin-converting enzyme 2 ( ACE2 ) and the host cell factor transmembrane serine protease 2 ( TMPRSS2 ). We cataloged the upper and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Proteases from all three of these categories are co-opted by SARS-CoV-2, and their presence in the host has important implications for both transmission of the virus and pathology. The expression of ACE2 and TMPRSS2 that is highly homologous to human ACE2 and TMPRSS2 is known to be an important susceptibility factor in animal infection with SARS-CoV-2 [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Additionally, many of the human proteases are polymorphic.…”
Section: Respiratory Proteasesmentioning
confidence: 99%
“…Proteases from all three of these categories are co-opted by SARS-CoV-2, and their presence in the host has important implications for both transmission of the virus and pathology. The expression of ACE2 and TMPRSS2 that is highly homologous to human ACE2 and TMPRSS2 is known to be an important susceptibility factor in animal infection with SARS-CoV-2 [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Additionally, many of the human proteases are polymorphic.…”
Section: Respiratory Proteasesmentioning
confidence: 99%
“…The S protein must undergo cleavage by proteases at the appropriate position to accomplish its fusion function [20]; it is cleaved by proprotein convertases such as the transmembrane protease serine 2 (TMPRSS2) and furin in the virus-producer cells. Recent studies have demonstrated that several other cellular proteases besides TMPRSS2 and furin can induce proteolytic cleavage of the S protein, such as TMPRSS4, trypsin-like proteases, and cathepsin L [21]. A hypothesis about a novel concept states that the cleavage of the S protein S1 subunit by furin results in a higher number of free S protein molecules, even with higher affinity than the original one, that can bind other ACE2 and other receptors in various tissues.…”
Section: Structural Composition Of Sars-cov-2 and Neuroinvasionmentioning
confidence: 99%
“…As with other members of the coronavirus family, it is known that angiotensin-converting enzyme 2 (ACE2) has a high affinity for the S protein from SARS-CoV-2 [22][23][24][25]. Differences in host susceptibility arise from the interaction between the receptor-binding domain and ACE2, while discrepancies in viral tropism and tissue distribution are likely determined by the distribution and abundance of ACE2 and TMPRSS2 and possibly other cellular proteases that are still under investigation [21]. To date, there are several studies focusing entirely on ACE2 as the major SARS-CoV-2 entry host receptor field [4], but research also shows ACE2 is expressed at very low levels in brain tissue, raising the question about other cofactors implicated in virus-host cell interactions in cells with low ACE2 expression [26].…”
Section: Structural Composition Of Sars-cov-2 and Neuroinvasionmentioning
confidence: 99%